Combination of an Autophagy Inducer and an Autophagy Inhibitor: A Smarter Strategy Emerging in Cancer Therapy - Liu, Ting; Zhang, Jing; Li, Kangdi; Deng, Lingnan; Wang, Hongxiang (Frontiers in Pharmacology, 2020)
Autophagy is considered a cytoprotective function in cancer therapy under certain conditions and is a drug resistance mechanism that represents a clinical obstacle to successful cancer treatment and leads to poor prognosis in cancer patients. Because certain clinical drugs and agents in development have cytoprotective autophagy effects, targeting autophagic pathways has emerged as a potential smarter strategy for cancer therapy. Multiple pre-clinical and clinical studies have demonstrated that autophagy inhibition augments the efficacy of anticancer agents in various cancers. Autophagy inhibitors, such as chloroquine and hydroxychloroquine, have already been clinically approved, promoting drug combination treatment by targeting autophagic pathways as a means of discovering and developing more novel and more effective cancer therapeutic approaches. We summarize current studies that focus on the antitumor efficiency of agents that induce cytoprotective autophagy combined with autophagy inhibitors. Furthermore, we discuss the challenge and development of targeting cytoprotective autophagy as a cancer therapeutic approach in clinical application Thus, we need to facilitate the exploitation of appropriate autophagy inhibitors and con-administration delivery system to cooperate with anticancer drugs. This review aims to note optimal combination strategies by modulating autophagy for therapeutic advantage to overcome drug resistance and enhance the effect of antitumor therapies on cancer patients.